2021
DOI: 10.1177/10775463211046676
|View full text |Cite
|
Sign up to set email alerts
|

Method for increasing the speed of an electrodynamic shaker for vibration test of rolling stock equipment

Abstract: The velocity required in IEC 61373 for long-life random vibration testing of Category-3 rolling stock equipment in the vertical direction is 2.7821 m/s, but the maximum velocity of existing electrodynamic shakers falls in the range of 2–2.5 m/s. In this study, an electrodynamic shaker with a velocity satisfying the requirements for vibration testing of Category-3 rolling stock equipment was developed. First, mechanical and equivalent circuit models of an electrodynamic shaker were developed. On this basis, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With the ongoing progress in agricultural machinery technology in China, the dissemination of intelligent and automated agricultural machinery has reached a broad scale. Among these machines, grain combine harvesters have been proven essential in crop harvest season [1][2][3]. It has been reported that the mainstay of China's agricultural sector consists of small-scale farmers, which comprise over 98% of the total population [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing progress in agricultural machinery technology in China, the dissemination of intelligent and automated agricultural machinery has reached a broad scale. Among these machines, grain combine harvesters have been proven essential in crop harvest season [1][2][3]. It has been reported that the mainstay of China's agricultural sector consists of small-scale farmers, which comprise over 98% of the total population [4,5].…”
Section: Introductionmentioning
confidence: 99%